2010
DOI: 10.1002/elan.200900578
|View full text |Cite
|
Sign up to set email alerts
|

A Glassy Carbon Electrode Modified with Multiwalled Carbon Nanotube/Chitosan Composite as a New Sensor for Simultaneous Determination of Acetaminophen and Mefenamic Acid in Pharmaceutical Preparations and Biological Samples

Abstract: A new chemically modified electrode is constructed based on multiwalled carbon nanotube/chitosan modified glassy carbon electrode (MWCNTs-CHT/GCE) for simultaneous determination of acetaminophen (ACT) and mefenamic acid (MEF) in aqueous buffered media. The measurements were carried out by application of differential pulse voltammetry (DPV), cyclic voltammetry (CV) and chronoamperometry (CA) methods. Application of DPV method showed that the linear relationship between oxidation peak current and concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…Due to the presence of reactive amino and hydroxyl functional group, CHT can be chemically modified and use for biosensor fabrication. Moreover, CHT is nontoxic, biocompatible, abundant and inexpensive [7][8][9][10][11]. Because CHT-CNTs can form a stable complex through noncovalent binding, the stability of CNTs in aqueous CHT solution was greatly improved.…”
Section: Introductionmentioning
confidence: 98%
“…Due to the presence of reactive amino and hydroxyl functional group, CHT can be chemically modified and use for biosensor fabrication. Moreover, CHT is nontoxic, biocompatible, abundant and inexpensive [7][8][9][10][11]. Because CHT-CNTs can form a stable complex through noncovalent binding, the stability of CNTs in aqueous CHT solution was greatly improved.…”
Section: Introductionmentioning
confidence: 98%
“…We have recently reported application of a glassy carbon electrode modified with multiwalled carbon nanotube/chitosan (MWCNTs-CHT) as a new sensor for simultaneous determination of paracetamol and mefenamic acid [1]. Our studies revealed that the oxidation peaks of the analytes were strongly overlapped at a glassy carbon electrode (GCE) but were well-separated, and had significantly higher currents, at the MWCNTs-CHT surface.…”
Section: Introductionmentioning
confidence: 79%
“…It can also cause skin rashes and inflammation of the pancreas [20]. Several analytical techniques such as titrimetry [16], spectrophotometry [21], spectrofluorometry [22], voltammetry [1], HPLC [23], TLC [24], colorimetry [25] and Fourier transform infra red spectroscopy [26] have been proposed for the determination of PAR.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(4-amino-benzoic acid) was used instead of Nafion to measure doxepin [256], polycysteic acid for sinomenine [257] and chitosan matrices either to measure acetaminophen and mefenamic acid simultaneously [258] or dipyrone [259]; in this latter case, the CNTs are covalently bound to the matrix [259]. Single-walled carbon nanotube (SWCNT)-and MWCNT-modified carbon ceramic electrodes were compared for nanomolar detection of acetaminophen [260], it being found that the current enhancement and electrocatalytic effects were better using SWCNT.…”
Section: Screen-printed Electrodesmentioning
confidence: 99%